Harvesting Patterns of Merang Mushroom on Planting Media Empty Fruit Bunch - Sarono Sarono; Sri Astuti; Devy Cendikia; Supriyanto Supriyanto; Sukamto Sukamto (Politeknik Negeri Lampung., 2023)
Empty fruit bunches (tankos) are a by-product, which is equal to the amount of CPO, which is 23%. Several attempts have been made to utilize tankos as a growing medium for mushroom, but these efforts have not been optimal. This is because they only take the edible mushroom product once, even though the waste still has the potential as a growing medium for the next mushroom, as well as the potential for compost. The purpose of the study was to determine the effect of new EFB, EFB that have been used once, and twice (used EFB I and used EFB II) on the pattern and daily production of straw mushrooms on the pilot plant scale.Pilot plant scale research has been carried out at CV Lintang Agro Farm Raman Adji East Lampung with three treatments, namely new EFB, used EFB I, and second-hand boarding houses. The study was repeated two times. The raw materials used are EFB, lime, katul, mushroom seeds, second-hand tankos I and second-hand EFB. The stages of the research process began with the preparation of EFB, the process of making edible mushrooms and observing the results of the research. The results showed that (1) EFB could be used as a planting medium for straw mushrooms 3 times, (2) the most productive production of straw mushrooms with EFB media was carried out until day 20 of the inoculation process, and (3) planting straw mushrooms on EFB media was able to reduce cellulose, hemicellulose, and lignin content significantly. Keywords: Pilot plant, EFB, Mushrooms, Harvest Pattern